2012
DOI: 10.1056/nejmsa1203980
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Local and Regional Variation in Health Care Spending

Abstract: Background Wide geographic variation in healthcare spending has generated concern about inefficiency and policy debate about geographic-based payment reform. Evidence on variation has focused on hospital referral regions (HRRs), which incorporate numerous local hospital service areas (HSAs). If there is substantial variation across local areas within HRRs, then policies focusing on HRRs may be poorly-targeted. Methods Using pharmacy and medical claims data from a 5% random sample of Medicare beneficiaries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 10 publications
4
86
1
Order By: Relevance
“…How large were these variations? A recent study of hospital service area-level variations in service use that analyzed 2007-2009 Medicare data found much less variation than we did; coefficients of variation were .09, .20, and .18 for monthly prescription fills, annual inpatient admissions, and annual outpatient office visits, respectively (9). That study is not directly comparable because we focused on mental health services for disabled Medicaid recipients with mental disorders and that study focused on health services for all Medicare recipients.…”
Section: Discussioncontrasting
confidence: 79%
“…How large were these variations? A recent study of hospital service area-level variations in service use that analyzed 2007-2009 Medicare data found much less variation than we did; coefficients of variation were .09, .20, and .18 for monthly prescription fills, annual inpatient admissions, and annual outpatient office visits, respectively (9). That study is not directly comparable because we focused on mental health services for disabled Medicaid recipients with mental disorders and that study focused on health services for all Medicare recipients.…”
Section: Discussioncontrasting
confidence: 79%
“…For instance, Zhang et al examined variation across 3,436 hospital service areas (HSAs) in the United States. They found that the highest spending HSAs were only loosely correlated with high spending HRRs [1]. These results suggest that targeting variation by HRR is neither a sensitive nor specific strategy to identify the source of unwarranted practice [1].…”
Section: Introductionmentioning
confidence: 99%
“…A PubMed search for "variation in care" yields over 23,000 entries (July 8,2013), and the same terms generate over 2 million results on Google Scholar (July 8, 2013). The seminal illustration of variation research, the Dartmouth Health Atlas, describes variation across 306 hospital referral regions (HRRs) in the United States [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRRs have not yet been suggested to be as useful for revealing substantial variation at local levels (Ashton et al, 1999;Zhang, Baik, Fendrick, & Baicker, 2012). However, the widely used HSAs in the U.S. were based on the 1992e93 data two decades ago (Center for Evaluative Clinical Sciences, 1999).…”
Section: Introductionmentioning
confidence: 99%